1996
DOI: 10.1258/002367796780744910
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anaesthesia with halothane and isoflurane in the rabbit: a comparison of the use of a face-mask or an anaesthetic chamber

Abstract: SummaryThe effects of induction of anaesthesia with halothane or isoflurane were studied in rabbits. The anaesthetic agents were delivered either via a face-mask, or the animals were placed in an anaesthetic induction chamber. All rabbits had periods of apnoea during induction, lasting 30-120 s, resulting in moderate hypercapnia and acidosis. Periods of apnoea were associated with a marked bradycardia. The combination of bradycardia and hypercapnia during induction may represent an increased risk of anaestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
3
20
0
1
Order By: Relevance
“…The use of inhalant anaesthetics as induction agents in rabbits is controversial as these might cause the animals to struggle and hold their breath during the induction phase. 36 Nevertheless, in this study rabbits accepted the anaesthesia induction technique well and endotracheal intubation could be performed without complications after desensitizing the larynx.…”
Section: Limitationsmentioning
confidence: 74%
“…The use of inhalant anaesthetics as induction agents in rabbits is controversial as these might cause the animals to struggle and hold their breath during the induction phase. 36 Nevertheless, in this study rabbits accepted the anaesthesia induction technique well and endotracheal intubation could be performed without complications after desensitizing the larynx.…”
Section: Limitationsmentioning
confidence: 74%
“…Rabbits are high risk anaesthesia patients, with a mortality risk 14 times higher than in dogs [3]. Possible reasons for this are that rabbits are easily stressed prey animals, they are difficult to intubate endotracheally and react to mask induction with volatile anaesthetics by extended breath-holding [4][5][6]. Rabbits have a large abdominal cavity in relation to the thoracic cavity, with the results that the pressure from the intestinal mass may interfere with respiration in dorsal recumbency during anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflurane, like other inhaled anesthesia, allows better control over the length and depth of anesthesia, as opposed to injectable anesthetics. It is believed to be safe and easy to maintain with a quick and uneventful recovery (24). It has been reported that isoflurane can inhibit the release of the excitatory neurotransmitter, glutamate from synaptosomes harvested from the cortex, but not hippocampus or striatum.…”
Section: Discussionmentioning
confidence: 99%